The assessment of the risk of falling and functional mobility of the elderly in their living environment - Lewko, Jolanta; Kamińska, Katarzyna; Doroszkiewicz, Halina; Talarska, Dorota; Sierakowska, Matylda; Krajewska-Kułak, Elżbieta (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. Falls are the major cause of injuries suffered by the elderly and, as a result, their disability, proneness to diseases and mortality. The objective of the study was to assess the functional mobility, the risk of falling and the ability to keep one’s balance by elderly persons in their living environment. Material and methods. The study was conducted among 100 randomly chosen persons over 65 in their living environment. The following standardized research tools were used: Barthel Index, Geriatric Depression Scale, “Timed, Up & Go”, One leg standing test. Results. The average age in the study group was 80.6 ± 6.4 years. In the oldest age group (81–90 years), the risk of falling was statistically significantly higher (p = 0.003) compared to younger age groups. Moreover, none of the subjects were able to do the balance test on their own (p = 0.02). Among the subjects with a diagnosed dementia, as many as 89% had a high risk of falling (p < 0.05) compared to the group of people not affected by dementia. There was no statistically significant relation between the age and the ability to keep one’s balance in the group of men. Conclusions. The occurrence of dementia significantly raises the risk of falling and decreases the ability to keep one’s balance. With age, functional mobility gets worse. In the study group, men had a better functional mobility than women. Nursing Topics 2014; 22 (2): 159–164